Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2017)
A dataset containing 30343330 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", "Country is France" ] } The dataset includes 30343330 records from 408 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0065043-160910150852091/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences